Polybrominated Diphenyl Ether (PBDE) Concentrations in Plasma of Pregnant Women from Western Australia - Stasinska, A.; Heyworth, J.; Reid, Alison; Callan, A.; Odland, J.; Duong, P.; Ho, Q.; Hinwood, A. (Elsevier, 2014)
PBDEs are a class of brominated flame retardants applied to consumer goods to reduce their flammability. These compounds are lipophilic, persistent and bioaccumulate through the food web. PBDEs have been detected in human blood, adipose tissue and breast milk. There are a small number of studies reporting concentrations of PBDEs in Australian populations. These indicate that concentrations are higher than in studies reporting concentrations from Europe but lower than those from Northern America. The aim of this paper was to determine the concentrations of PBDEs in the plasma of pregnant women participating in the Australian Maternal Exposure to Toxic Substances (AMETS) study in Western Australia. The samples comprised 164 pregnant women, aged 18 years and over, who were non-smokers and not occupationally exposed to persistent substances. Participants provided blood samples at 38 weeks gestation and these were analysed for five PBDE congeners. Maternal health and birth outcomes data were also obtained.The median for sum PBDE concentrations in plasma was 53.9 pg g− 1 (range 13.2 to 1390 pg g− 1 ww). Concentrations were adjusted for the estimated plasma lipid content. The concentrations of Σ5PBDE ranged from 2.44 to 258 ng g− 1 lipid with a median of 9.97 ng g− 1 lipid. BDE-47 was the dominant congener (median 21.4 pg g− 1, range < 4.95 to 1030 pg g− 1) followed by BDE-153 (median 12.2 pg g− 1, range < 2.94 to 353 pg g− 1). There were no significant associations between maternal, housing or dietary factors and concentrations of PBDEs in this study. Maternal PBDE concentrations were not associated with infant birth weight. This study builds upon previous Australian research and shows that concentrations in this sample of Western Australian women were higher than in parts of Europe.